Role of State Authorities in Preserving Industrial Heritage of Chelyabinsk Region (1960s-1980s) - E. S. Lakhtionova (Научный диалог, 2024)
This article aims to identify the role and contribution of state authorities in the Chelyabinsk region during the 1960s-1980s in preserving industrial heritage sites. The relevance of this study is driven by the urgent need to draw attention of governmental structures to the issue of destruction of remaining monuments of industrial past. The primary sources utilized are archival materials concentrated in the Unified State Archive of the Chelyabinsk region, with many documents being introduced into scholarly circulation for the first time. The scientific novelty of the article lies in the absence of prior research on this topic. The tasks of state bodies in the field of monument protection according to existing regulatory acts of the specified period are identified. The research demonstrates that the most significant contribution was made towards identification, registration, and study of industrial heritage sites, with 43 objects receiving monument status by 1989. However, activities related to repair, restoration, and museumification of registered monuments proved less productive, as only one industrial heritage site had been museumified by 1989. This was attributed to insufficient oversight by state authorities regarding the preservation and utilization procedures of registered monuments.